Epidemiological landscapes in the Amazon: exploring the association between land use, environmental indicators, and vector-borne diseases - Ana Claudia Rorato Vitor; Cláudia Torres Codeço; Maria Isabel Sobral Escada (Cadernos de Saúde Pública)
Abstract: This study investigates the characteristics of municipalities in the Legal Amazon that may be associated with the incidence of vector-borne diseases using environmental and land use indicators and cluster analysis. We identified and described six groups of Amazonian municipalities with similar environmental and agrarian characteristics. Based on a set of epidemiological indicators, we explore the incidence of neglected vector-borne tropical diseases in these groups. Results show a great environmental heterogeneity in the Amazonian municipalities, with well-defined profiles in the obtained groups. Moreover, they show the relation of economic activities and environmental degradation with the spread of diseases. This approach can comprehensively show the environmental and health challenges of regions, contributing to the development of more effective conservation strategies to be adapted to the specific needs of each municipality profile.